2, 3‐Dihydroxybenzoic Acid Decarboxylase from Fusarium oxysporum: Crystal Structures and Substrate Recognition Mechanism. (2nd July 2020) - Song, Mengkun; Zhang, Xuemei; Liu, Weidong; Feng, Jinghui; Cui, Yunfeng; Yao, Peiyuan; Wang, Min; Guo, Rey‐Ting; Wu, Qiaqing; Zhu, Dunming
Abstract: A 2, 3‐dihydroxybenzoic acid decarboxylase from Fusarium oxysporum (2, 3‐DHBD_Fo) has a relatively high catalytic efficiency for the decarboxylation of 2, 3‐dihydroxybenzoic acid (DHBA) and carboxylation of catechol, thus it has a different substrate spectrum from other benzoic acid decarboxylases. We have determined the structures of 2, 3‐DHBD_Fo in its apo form and complexes with catechol or 2, 5‐dihydroxybenzoic acid at 1.55, 1.97, and 2.45 Å resolution, respectively. The crystal structures of 2, 3‐DHBD_Fo show that the enzyme exists as a homotetramer, and each active center has a Zn 2+ ion coordinated by E8, H167, D291 and three water molecules. This is different from 2, 6‐DHBD from Rhizobium sporomusa, in which the Zn 2+ ion is also coordinated with H10. Surprisingly, mutation of A10 of 2, 3‐DHBD_Fo to His resulted in almost complete loss of the enzyme activity. Enzyme‐substrate docking and site‐directed mutation studies indicate that residue R233 Δ interacts with the 3‐hydroxy group of 2, 3‐DHBA, and plays an important role in substrate recognition for this enzyme, thus revealing the molecular basis 2, 3‐dihydroxybenzoic acid decarboxylase. Abstract : It depends on your position : Crystal structure and mutation studies reveal that R233 Δ plays an important role in the substrate recognition of 2, 3‐dihydroxybenzoic acid decarboxylase (DHBD) from Fusarium oxysporum, as well as the molecular basis for this enzyme being a 2, 3‐DHBD with different substrate preference from known 2, 6‐DHBDs and salicylic acid decarboxylases.